Radiation resistance of paralytic shellfish poison (PSP) toxins - San Juan, Edith M.; Acevedo, Teresita P. (2000)
Radiation resistance of paralytic shellfish poison (PSP) toxins, obtained from Pyrodinium bahamese var. compressum in shellstocks of green mussels, was determined by subjecting the semi-purified toxin extract as well as the shellstocks of green mussels to high doses of ionizing radiation of 5, 10, 15 and 20 kGy. The concentration of the PSP toxins was determined by the Standard Mouse Bioassay (SMB) method. The radiation resistance of the toxins was determined by plotting the PSP toxin concentration versus applied dose in a semilog paper. The D10 value or decimal reduction dose was obtained from the straight line which is the dose required to reduce the toxicity level by 90%. The effects of irradiation on the quality of green mussels in terms of its physico-chemical, microbiological and sensory attributes were also conducted. The effect of irradiation on the fatty acid components of green mussels was determined by gas chromatography. Radiation resistance of the PSP toxins was determined to be lower in samples with initially high toxicity level as compared with samples with initially low toxicity level. The D10 values of samples with initially high PSP level were 28.5 kGy in shellstocks of green mussels and 17.5 kGy in the semi-purified toxin extract. When the PSP level was low initially, the D10 values were as high as 57.5 and 43.5 kGy in shellstocks of green mussels for the two trials, and 43.0 kGy in semi-purified toxin extract. The microbial load of the irradiated mussels was remarkably reduced. No difference in color and odor characteristics were observed in the mussel samples subjected to varying doses of ionizing radiation. There was darkening in the color of the mussel meat and its juice. The concentration of the fatty acid components in the fresh green mussels were considerably higher as compared with those present in the irradiated mussels, though some volatile fatty acids were detected as a result of irradiation.
Thesis (M.S. Food Science)
Keywords: Saxitoxin -- Philippines -- Limay (Bataan).; Mussels -- Effect of radiation on -- Philippines -- Limay (Bataan)